Alteration of Hyaluronic Acid Metabolism in Tumor Microenvironment Can Modulate DNA Repair Gene Expression: Therapeutic Potential for Triple-Negative Breast Cancer - Sevic, Ina (2025)
Breast and colorectal cancers remain among the leading causes of cancer-related deaths globally, with therapy failure often driven by tumor complexity and interactions with the tumor microenvironment (TME). Hyaluronic acid (HA), a key extracellular matrix component, plays a vital role in TME remodeling, while altered breast cancer gene 1 and 2 (BRCA1/2) expression, essential for DNA repair, is linked to cancer aggressiveness. This study investigates the link between HA metabolism and BRCA1/2 expression in breast and colorectal cancers. We analyzed HA, CD44, and BRCA1 and 2 expression in patient tissue samples via immunofluorescence. To assess whether HA metabolism affects BRCA1/2 expression, we treated spheroids with hyaluronidase (HYAL) and 4-methylumbelliferone (4-MU) to reduce HA levels. The resulting changes in BRCA1/2 expression were evaluated using qPCR, and tumor profiles were assessed through microscopy and immunofluorescence. We found a coordinated behavior between BRCA1 and BRCA2 in breast cancer and observed BRCA1’s crypt-restricted expression in normal colorectal tissue, which may underlie its well-known tissue specificity. In a triple-negative breast cancer model, we observed that 4-MU reduced spheroid volume and increased BRCA 1/2 levels, suggesting a potential mechanism of 4-MU for tumor shrinkage and BRCA restoration. These findings suggest that 4-MU, a compound already approved for oral use in hepatobiliary indications in Europe and Asia, is a mechanistically plausible HA-targeting candidate for therapeutic repurposing in BRCA-deficient tumors.